Hubungan Gaya Hidup, Dukungan Keluarga dan Peran Petugas Kesehatan Serta Kepatuhan Mengkonsumsi Obat Anti Hipertensi pada Pasien Prolanis Hiperetensi dengan Tekanan Darah Terkontrol di Puskesmas Tembiahan Kota Tahun 2023 - Mulkiya, Annisa Usraina; Harahap, Heryudarini; Mitra, Mitra; Marlina, Hastuti; Devis, Yessica (Universitas Batanghari Jambi, 2024)
The prevalence of high blood pressure in the population aged 18 years and above increased from 25.8% to 34.1%. The significant increase in cases of non-communicable diseases is expected to increase the burden on society and government, because handling it requires large costs and requires high technology. The purpose of this study was to determine the relationship between lifestyle, family support and the role of health workers and compliance with taking medication with controlled blood pressure at the Tembilahan City Health Center in 2023. The research method uses quantitative methods with a Cross Sectionl design approach. The number of samples in this study amounted to 160 hypertension prolanis patients. The sample technique used was Proposional stratified Random Sampling. Data collection through primary data by distributing questionnaires with independent variables (diet, smoking habits, physical activity, stress conditions, family support, the role of health workers and compliance with drug consumption) and the dependent variable is controlled blood pressure. The results of this study indicate that there is a significant relationship between adherence to taking anti-hypertensive drugs (p value = 0.000 and OR 14.744), smoking habits (p value = 0.000 and OR 7.082), diet (p value = 0.000 and OR 4.899), family support (p value = 0.012 and OR 2.977), with controlled blood pressure in hypertension prolanis patients. The variable of adherence to taking anti-hypertensive drugs is the dominant factor that most influences controlled blood pressure in hypertension prolanis patients with an OR value of 14.744.